Education, school and school mathematics: meanings of the basic education mathematics teachers (Educação e Pesquisa, 2021)
The mathematics teacher initial training has been the subject of discussion in the governmental spheres and in the Brazilian Societies of Mathematical Education and of Mathematics. As a consequence of this, we notice advances in some critical points, among which stands out - the excess of academic mathematics disarticulated from the school mathematics; and - the approximation of the mathematics education theoretical-methodological trends with the mathematics undergraduate courses curricular organization. However, there are still absent the conversations involving the different and varied dimensions that interfere in the teaching and learning process of school mathematics; and the different curriculum theories. As a result, the neutrality of mathematical knowledge and the excessive concern with the normative dimension of the curriculum continue being protagonists in the mathematics teacher initial training. In this sense, this article aimed to investigate aspects related to the perception and understanding of basic education mathematics teachers about the school subjects, the school, the school education and about being a math teacher. Methodologically, it is included in a quali-quantitative research approach, in which, in order to achieve the project’s objectives, a field research, through a questionnaire available in the “Google docs”, was carried out with the public network mathematics teachers from São Paulo state. Theoretically, it was based on studies about curriculum theories. It was tangible that the collaborating teachers are still very attached to the normative dimension of the curriculum, always prioritizing what to teach, how to teach and how to evaluate, without worrying about other dimensions (cultural, social, political) that interfere in the curriculum organization.of the school mathematics.